The experiences of students from refugee backgrounds at universities – reflections on the social, emotional and practical challenges - Joyce, A.; Earnest, Jaya; de Mori, Gabriella; Silvagni, G. (Oxford University Press, 2010)
The vast majority of refugees arriving in Australia are between the ages of 16 and 35 years, and some refugee youth are embarking on university education. While there has been research conducted on refugee youth experiences at secondary school there is little research about their experiences in university education. Most refugee youth have experienced a range of traumatic experiences that compound the difficulties in adjusting to a new country. Many of these youth have experienced disrupted schooling in the past and have to take on household duties that make secondary education difficult in their resettled countries. Currently, it is unknown to what extent these challenges are also experienced by refugee tertiary students and if there are other challenges that are unique to the university environment. This paper reports on the findings of a study undertaken with students from refugee backgrounds studying at university in Victoria and Western Australia, Australia. Focus groups and in-depth interviews were used in the study to capture the voices and perceptions of refugee students. The results reveal that refugee students experience a variety of difficulties and barriers to success that are often not recognized by universities.